Extensive Drug-Resistant Salmonella enterica Isolated From Poultry and Humans: Prevalence and Molecular Determinants Behind the Co-resistance to Ciprofloxacin and Tigecycline - Abd El-Aziz, Norhan K.; Tartor, Yasmine H.; Gharieb, Rasha M. A.; Erfan, Ahmed M.; Khalifa, Eman; Said, Mahmoud A.; Ammar, Ahmed M.; Samir, Mohamed (Frontiers in Microbiology, 2021)
Abstract The emergence of extensive drug-resistant (XDR) Salmonella in livestock animals especially in poultry represents a serious public health and therapeutic challenge. Despite the wealth of information available on Salmonella resistance to various antimicrobials, there have been limited data on the genetic determinants of XDR Salmonella exhibiting co-resistance to ciprofloxacin (CIP) and tigecycline (TIG). This study aimed to determine the prevalence and serotype diversity of XDR Salmonella in poultry flocks and contact workers and to elucidate the genetic determinants involved in the co-resistance to CIP and TIG. Herein, 115 S. enterica isolates of 35 serotypes were identified from sampled poultry (100/1210, 8.26%) and humans (15/375, 4.00%), with the most frequent serotype being S. Typhimurium (26.96%). Twenty-nine (25.22%) S. enterica isolates exhibited XDR patterns, 25 out of them (86.21%) showed CIP/TIG co-resistance. Exposure of CIP and TIG resistant isolates to the carbonyl cyanide 3-chlorophenylhydrazone (CCCP) efflux pump inhibitor resulted in an obvious reduction in their minimum inhibitory concentrations (MICs) values and restored the susceptibility to CIP and TIG in 17.24% (5/29) and 92% (23/25) of the isolates, respectively. Molecular analysis revealed that 89.66% of the isolates contained 2-6 plasmid-mediated quinolone resistance genes with the predominance of qepA gene (89.66%). Mutations in the gyrA gene were detected at codon S83 (34.62%) or D87 (30.77%) or both (34.62%) in 89.66% of XDR Salmonella. The tet(A) and tet(X4) genes were detected in 100% and 3.45% of the XDR isolates, respectively. Twelve TIG-resistant XDR Salmonella had point mutations at codons 120, 121, and 181 in the tet(A) interdomain loop region. All CIP and TIG co-resistant XDR Salmonella overexpressed ramA gene, 17 (68%) out of them harbored 4-bp deletion in the ramR binding region (T-288/A-285). However, four CIP/TIG co-resistant isolates overexpressed the oqxB gene. In conclusion, the emergence of XDR S. enterica in poultry and humans exhibiting CIP/TIG co-resistance with no previous exposure to TIG deemed the urgent need to reduce the unnecessary antimicrobial use in poultry farms in Egypt.